Faktor-Faktor yang Mempengaruhi Efisiensi Teknis Relatif dan Sikap Petani dalam Menghadapi Resiko Produksi pada Usahatani Padi Sawah di Lahan Beririgasi Teknis - Nizwar Syafa'at (Jurnal Agro Ekonomi, 1990)
The study is based on an indication that different farm productivity among farmers in the same agro-ecosystem is caused by different farmers ability to adopt technology of rice production. Technology adoption can be measured by technical production efficiency level and farmers attitude in dealing with production risk in using anorganic fertilizer. The study will identify determinants of technical production efficiency level and farmers attitude in dealing with the use of that anorganic fertilizer. Those determinants consist of some economic, social and institutional factors. The study is a case study in WKPP Manyeti in Kabupaten Subang. The results of the study are as follows: (a) Educational level, and number of households members are not related to technical production efficiency level; (b) Off-farm income and employment level in off-farm activities are positively related to technical production efficiency level. Income from non-rice production activities and employment level in non-rice production activities are not related to technical production efficiency level; (c) Farmers with off-farm labor activities are risk preference and farmers in this category are more secure in dealing with production failure; (d) technical production efficiency level for both owner operators and tenants are equal; (e) Owner operatore and tenants are risk preference in using anorganic fertilizers. Gadai farmers are risk averter.